First Line Therapy for Metastatic Pancreatic Cancer - Jarboe, Jamie; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Metastatic pancreatic cancer remains a difficult disease to treat; however, there are more new drug combinations on the horizon each week. We will discuss the results of the MPACT trial presented at the 2013 ASCO Annual Meeting (Abstracts #4005, #4058, and #4059) and compare to the 2011 FOLFIRINOX data. Image: MPACT control and experimental arms.